The Effectiveness of Cucumber Juice on Hypertension Patients Blood Pressure: Efektivitas Jus Mentimun Terhadap Tekanan Darah Pasien Hipertensi - Suryarinilsih, Yosi; Putri, Hanifa; Roza, Defia (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Hypertension is currently one of the non-communicable diseases which is a very serious health problem. The prevalenceof hypertension in West Sumatra was recorded at 25.16% of the national prevalence of 34.1%. Management ofhypertension is through pharmacological therapy, namely by taking medication for life, and can also be accompanied bynon-pharmacological therapy, one of which is cucumber juice therapy. The research aims to determine the effectivenessof cucumber juice on blood pressure in hypertensive patients. The research used a quasi-experimental method (one grouppre-post test design). Conducted in Surau Gadang Village, Padang City with a sample size of 11 people obtained throughpurposive sampling technique. The pre-test results showed that the average systolic blood pressure was 145.45 mmHgand the average diastolic blood pressure was 81.82 mmHg and the post-test results showed that the average systolicblood pressure was 121.82 mmHg and the average diastolic blood pressure was 71. 82 mmHg. Conclusion Cucumberjuice is effective in reducing blood pressure in hypertensive patients. It is hoped that health workers, especially nurses,can provide health education about the use of cucumbers as a form of hypertension therapy.